2002
DOI: 10.1016/s0735-1097(02)02683-9
|View full text |Cite
|
Sign up to set email alerts
|

Isometric arm counter-pressure maneuvers to abort impending vasovagal syncope

Abstract: Isometric arm contraction is able to abort impending vasovagal syncope by increasing systemic BP. Arm counter-pressure maneuvers can be proposed as a new, feasible, safe, and well accepted first-line treatment for vasovagal syncope.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
110
1
6

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 190 publications
(125 citation statements)
references
References 20 publications
4
110
1
6
Order By: Relevance
“…Brignole et al evaluated the cardiovascular response to handgrip and arm-tensing in healthy subjects and contrary to our results, found a maximum increase in SBP after 2 min of the maneuver of 31±16 mmHg for handgrip and 32±18 mmHg for arm-tensing. 20 A possible explanation for this difference in results is that the duration of handgrip was much longer in their study than in ours (2 min vs 30 s). Our results suggest that squatting and leg-crossing with muscle tensing are more effective than handgrip.…”
Section: Discussioncontrasting
confidence: 59%
See 1 more Smart Citation
“…Brignole et al evaluated the cardiovascular response to handgrip and arm-tensing in healthy subjects and contrary to our results, found a maximum increase in SBP after 2 min of the maneuver of 31±16 mmHg for handgrip and 32±18 mmHg for arm-tensing. 20 A possible explanation for this difference in results is that the duration of handgrip was much longer in their study than in ours (2 min vs 30 s). Our results suggest that squatting and leg-crossing with muscle tensing are more effective than handgrip.…”
Section: Discussioncontrasting
confidence: 59%
“…At the onset of these symptoms, physical maneuvers that increase venous return and sympathetic tone may abort the syncopal attack. [19][20][21][22] Brignole et al proposed handgrip as a method of treating vasovagal syncope, 20 and Croco et al also reported a favorable effect of isometric arm exercise in aborting impending vasovagal syncope. 21 However, in our study, handgrip prevented impending syncope in only 1 patient and the other 7 patients fainted despite doing handgrips, which is a similar result to that of Krediet et al 22 who found that handgrip had only a trivial effect on the fainting response.…”
Section: Discussionmentioning
confidence: 99%
“…Physical countermaneuvers that involve the tensing of muscle groups in the arms and legs have been shown to reduce syncope burden if used early in the prodrome period [23][24][25]. As the effect of gravity is a major contributor to syncope, the easiest of these countermaneuvers is assumption of a supine position.…”
Section: Physical Countermaneuversmentioning
confidence: 99%
“…Two initial studies demonstrated that arm tensing and leg crossing raised blood pressure 30% to 60% and postponed or prevented symptoms on tilt-table testing [15,16]. The subsequent Physical Counterpressure Maneuvers Trial (PC Trial) randomized 223 patients with NCS and prodromal symptoms to PCM or conventional therapy, blinding patients to randomization allocation.…”
Section: Effectiveness Of Non-pharmacological Treatment (And the Placmentioning
confidence: 99%